Ductile fracture assessment of high-density polyethylene (HDPE-PE100) weakened by an inclined double keyhole notch. (December 2019) - Soltaninezhad, S.; Salavati, H.; Soltani Goharrizi, A.
Highlights: Mixed mode fracture experiments on keyhole notch specimens made of high density polyethylene (HDPE-PE100) are provided. A criterion based on the averaged value of strain energy density in combination with equivalent material concept is proposed to predict ductile fracture of keyhole notch specimens made of HDPE-PE100 under mixed mode condition. The averaged strain energy density criterion is able to predict the mixed-mode fracture of keyhole notched HDPE-PE100 specimens with a considerable accuracy. The effect of notch geometry on fracture load is theoretically elaborated. Abstract: High-Density Polyethylene (HDPE-PE100) material has a ductile behavior and is used in a wide range of industries. In this article, the Strain Energy Density (SED) averaged over a well-defined control volume at a notch edge was applied in combination with the Equivalent Material Concept (EMC) to assess the ductile fracture behavior of keyhole-notched specimens made of High-Density Polyethylene (HDPE-PE100) material under mixed-mode loading. An experimental program was performed and 54 new experimental data were totally provided. Additionally, different mode mixities were regarded by changing the inclination angles of the notches with respect to the applied load directions. The results obtained from the mentioned criteria were in good agreement with those of the experimental data.